2019
DOI: 10.1093/nar/gkz469
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of spinal muscular atrophy mouse models with AAV9-Exon-specific U1 snRNA

Abstract: Spinal Muscular Atrophy results from loss-of-function mutations in SMN1 but correcting aberrant splicing of SMN2 offers hope of a cure. However, current splice therapy requires repeated infusions and is expensive. We previously rescued SMA mice by promoting the inclusion of a defective exon in SMN2 with germline expression of Exon-Specific U1 snRNAs (ExspeU1). Here we tested viral delivery of SMN2 ExspeU1s encoded by adeno-associated virus AAV9. Strikingly the virus increased SMN2 exon 7 inclusion and SMN prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 57 publications
3
31
0
Order By: Relevance
“…In this study, through the exploitation of a pre-existing mouse model of acute HT1 directly linked to a splicing defect, we provided the early proof-of-principle that a compensatory U1snRNA can rescue FAH splicing and protein expression in vivo. Moreover, the compensatory U1 F , albeit targeting the 5 ss, appeared to guarantee a remarkable gene specificity, comparable to that previously demonstrated for the Exon Specific U1snRNA (ExSpeU1) targeting poorly conserved intronic sequences [13,20]. This observation strengthens the potential of the compensatory U1snRNA variants that, in most exon contexts, are much more effective than ExSpeU1s.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, through the exploitation of a pre-existing mouse model of acute HT1 directly linked to a splicing defect, we provided the early proof-of-principle that a compensatory U1snRNA can rescue FAH splicing and protein expression in vivo. Moreover, the compensatory U1 F , albeit targeting the 5 ss, appeared to guarantee a remarkable gene specificity, comparable to that previously demonstrated for the Exon Specific U1snRNA (ExSpeU1) targeting poorly conserved intronic sequences [13,20]. This observation strengthens the potential of the compensatory U1snRNA variants that, in most exon contexts, are much more effective than ExSpeU1s.…”
Section: Discussionsupporting
confidence: 83%
“…The expression of the splicing-defective human transgene in wild-type mice has been previously exploited to create surrogate models of coagulation factor VII or IX deficiency [7,12], which demonstrated the correction ability of the U1snRNA variants. Only recently it was shown that the delivery of an engineered U1snRNA by adeno-associated virus (AAV) rescues splicing and protein expression and, most importantly, the disease phenotype and survival in a mouse model of spinal muscular atrophy (SMA) [20].…”
Section: Introductionmentioning
confidence: 99%
“…An important concern for ExSpeU1s, as well as for other splicing correction strategies with ASO or chemical compounds, is their potential off-target effects. Previous studies in cellular and animal models with one ExSpeU1 active on Spinal Muscular Atrophy identified a very limited number of off-targets by RNA-Seq analysis (Dal Mas, Rogalska, et al, 2015;Donadon et al, 2019). Indeed, the availability of cellular systems that overexpress the ExSpeU1s will allow the identification of the most promising and safe molecules active on the different CFTR exons.…”
Section: Discussionmentioning
confidence: 99%
“…It was previously shown that their binding downstream affected exons corrects aberrant splicing in several cellular (Alanis et al, 2012;Dal Mas, Fortugno, et al, 2015;Nizzardo et al, 2015;Tajnik et al, 2016) and mouse models (Balestra et al 2014;Dal Mas, Rogalska, et al 2015;Balestra et al 2016;Rogalska et al 2016;Donadon et al 2018). Strikingly, an ExSpeU1 delivered by Adeno Associated Virus (AAV) resulted to an effective and safe therapy in a Spinal Muscular Atrophy (SMA) mouse model extending the survival from 10 days to˜6 months (Donadon et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the use of in vivo disease models allows investigators to observe and analyze symptomatic manifestation of NDDs alongside with the therapeutic outcomes of their experimental treatment. This also aids in getting a comprehensive insight into the complex interconnection between etiological and symptomatic changes during the progression of NDDs, such as neuronal ceroid lipofuscinosis (NCL or Batten disease) [35], spinal muscular atrophy [101], or Niemann-Pick disease [102], whose development is typically associated with genetic perturbations in multiple genes. Therefore, in contrast to in vitro models, a mouse model of NDD would allow recapitulating onset and progression of the counterpart human disease of a given degree of severity.…”
Section: In Vitro Vs In Vivo Modelsmentioning
confidence: 99%